The Roma/Non-Roma Test Score Gap in Hungary - Kertesi, Gábor; Kézdi, Gábor (American Economic Review, 2011)
This paper documents and decomposes the test score gap between Roma and non-Roma 8th graders in Hungary in 2006. Our data connect national standardized test scores to an individual panel survey with detailed data on ethnicity and family background. The test score gap is approximately one standard deviation for both reading and mathematics, which is similar to the gap between African-American and White students of the same age group in the US in the 1980s. After accounting for on health, parenting, school fixed effects and family background, the gap disappears in reading and drops to 0.15 standard deviation in mathematics.